Coping with Diverse Semantic Models when Routing Ubiquitous Computing Information - SONG, GUO (My University, 2008)
Routing of contextual information within ubiquitous computing environments is a key challenge that must be tackled for such environments to be successful. It is accepted that such routing systems need to cope with mobile and volatile sources and destinations of contextual information, and semantic-based publish subscribe systems have been proposed as a means to support this. However such systems typically assume a common semantic model underpinning the routing which limits their ability to cope with heterogeneity. In contrast, the authors have developed a semantic-based publish subscribe system that is unique in allowing several semantic models to support routing. It is known from previous work that the number of semantic models in memory directly impacts on performance of routing, and that different loading strategies are needed, the selection of which is influenced by: the characteristics of the semantic model itself, the applications using the system and the network environment. This paper however just focuses on the experiments that have been undertaken to determine the key semantic model characteristics that may influence the selection of which loading strategy to use.
PUBLISHED
Keywords: publish-subscribe; semantic modelling